Non-alcoholic fatty liver disease (NAFLD) and COVID-19 outcomes: A systematic review, meta-analysis, and meta-regression - Kurniawan, Andree; Hariyanto, Timotius I. (Narra Sains Indonesia, 2023)
It is important to identify risk factors for poor outcomes of coronavirus disease 2019 (COVID-19) patients. Currently, the correlation between non-alcoholic fatty liver disease (NAFLD) and COVID-19 outcomes has not been established. This study was conducted to determine the association between NAFLD and in-hospital outcomes of COVID-19 patients. The systematic searches were conducted by using PubMed and the Europe PMC databases and particular keywords were used as of December 10, 2020. Further searches were conducted up to 2022. All articles that include data about COVID-19 and fatty liver disease were collected. Statistical analysis was performed by using Review Manager 5.4 and Comprehensive Meta-Analysis version 3 software. A total of 7,210 COVID-19 patients from 18 studies were included in the final analysis. Meta-analysis revealed that NAFLD increased the risk of developing poor in-hospital outcome (pooled both severe disease and death) in COVID-19 patients (RR 1.42; 95%CI: 1.17–1.73, p<0.001, I2=84%, random-effect modeling). Subgroup analysis however found that having NAFLD only increased the chance of getting severe COVID-19 (RR 1.67; 95%CI: 1.32–2.13, p<0.001, I2=86%, random-effect modeling) and not mortality (RR 1.00; 95%CI: 0.68–1.47, p=0.98, I2=80%, random-effect modeling). Meta-regression suggested that age (p=0.001) and diabetes (p=0.029) were significantly influenced the relationship between NAFLD and in-hospital outcomes of COVID-19 (pooled both severe disease and mortality). The weaker association of NAFLD and in-hospital outcomes of COVID-19 was found for studies with median age ≥45 years old (RR 1.29) when compared to studies with median age <45 years old (RR 2.96). In addition, studies with the prevalence of diabetes ≥25% (RR 1.29) had a weaker association with in-hospital outcomes when compared to studies with diabetes prevalence <25% (RR 1.85). In conclusion, NAFLD increased the risk of chance of getting severe COVID-19 and therefore it should be evaluated closely to reduce the chance of getting severe COVID-19.